Handbook of fillers - Wypych, George (ChemTec Publishing, 2016)
Handbook of Fillers, Fourth Edition, discusses the rapidly advancing field of fillers, the substances added to plastics and composites that add value by improving and modifying the properties of materials and reducing costs. This new edition is an essential reference for engineers and scientists using fillers in a range of materials, including plastics, rubber, adhesives, and paper. The book is designed to be a comprehensive reference for both experienced practitioners and those new to fields where fillers are used. It covers available fillers and their properties, their effect on filled materials, such as mechanical properties, rheology, morphology, flammability, and recycling, and their use in practical applications. In particular, this new edition provides extensive coverage of nanofillers, along with the practical information needed to deploy these new technologies in the real world. The book includes the latest advances in filler technology, with consolidated technical information from over 4,000 research papers, data from over 160 filler and equipment manufacturers, and a thorough review of the patent literature.
Keywords: Fillers (Materials); Fillers (Materials) -- Handbooks, manuals, etc.; elektronické knihy; electronic books